Influence of temperature and packaging type on quality parameters and antimicrobial properties during Yateí honey storage - Martínez, Ramón Alejandro (2017)
Fil: Martínez, Ramón Alejandro. Universidad Nacional de Misiones. Facultad de Ciencias Exactas, Químicas y Naturales. Módulo de Bioquímica y Farmacia; Argentina.